2021
DOI: 10.1155/2021/8857329
|View full text |Cite
|
Sign up to set email alerts
|

Rutaecarpine Ameliorates Pressure Overload Cardiac Hypertrophy by Suppression of Calcineurin and Angiotensin II

Abstract: Cardiac hypertrophy is a major pathological process to result in heart failure and sudden death. Rutaecarpine, a pentacyclic indolopyridoquinazolinone alkaloid extracted from Evodia rutaecarpa with multiple pharmacological activities, yet the underlying protective effects and the mechanisms on cardiac hypertrophy remain unclear. This study aimed to evaluate the potential effects of rutaecarpine on pressure overload cardiac hypertrophy. Cardiac hypertrophy in rat was developed by abdominal aortic constriction (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 19 publications
1
3
0
Order By: Relevance
“…[12]. Numerous studies have confirmed that RUT demonstrated positive effects on HepG2 cells, macrophages, colitis, and gastric mucosa protection [13]. In addition, we have reported that RUT protects against ethanol-induced acute gastric ulcers before [14].…”
Section: Introductionsupporting
confidence: 52%
See 1 more Smart Citation
“…[12]. Numerous studies have confirmed that RUT demonstrated positive effects on HepG2 cells, macrophages, colitis, and gastric mucosa protection [13]. In addition, we have reported that RUT protects against ethanol-induced acute gastric ulcers before [14].…”
Section: Introductionsupporting
confidence: 52%
“…The severity of gastric atrophy may be influenced by the inhibition of the SHH signaling pathway by IL-1β, which may inhibit gastric-acid secretion and intracellular calcium release (Figure 10). The corpus glands that are closer to the rat forestomach exhibit consistently high levels of expression of SHH protein [13]. Additionally, IL-1β is the strongest inhibitor of gastric acid found thus far, and the continuous secretion of low levels of gastric acid into the stomach will promote the occurrence and development of atrophy and lead to an increase in the risk of development of GC [28].…”
Section: Discussionmentioning
confidence: 99%
“…With regard to the herb itself, potential cardiotoxicity might be related to bioactive substances with the dual characteristics of efficacy and toxicity, such as evodiamine and rutaecarpine. On the one hand, evodiamine and rutaecarpine can produce beneficial pharmacodynamic and pharmacological effects for anti-arrhythmia, myocardial protection and recovery, as evidenced by previous research based on experiments around isolated atria in guinea pigs, cardiac fibrosis in mice, and myocardial ischemia-reperfusion injury and cardiac hypertrophy in rats (Kobayashi et al, 2001;Rang et al, 2004;Jiang et al, 2017;Tian et al, 2019;Li et al, 2021;Zhan et al, 2021). On the other hand, the toxicological effects of evodiamine on the heart, which might be associated with oxidative stress, have been observed through in vivo and in vitro experiments with primary neonatal rat cardiomyocytes and zebra fish (Yang et al, 2017).…”
Section: Introductionmentioning
confidence: 94%
“…Rutaecarpine [8,13-dihydroindolo (2',3': 3,4) pyrido (2,1-b) quinazolin-5 (7H)-one, RUT, 1, Figure 1] is a pentacyclic indolopyridoquinazolinone first isolated by Asahina and Kashiwaki from Evodia rutaecarpa (Qiu, 2012), which is one of the most frequently used traditional Chinese herbs for treating diverse ailments, including headaches, gastrointestinal disorders, postpartum hemorrhage, amenorrhea, difficult menstruation, and other diseases (Lee et al, 2008;Liao et al, 2011). As one of the most abundant compounds in Evodia rutaecarpa, RUT has also been demonstrated to possess a broad spectrum of intriguing pharmacological activities, including anti-inflammation (Moon et al, 1999), anti-platelet (Sheen et al, 1996;Sheu et al, 1996), vasodilatory (Chiou et al, 1994;Li et al, 2021), analgesic (Zhang et al, 2017;Zhang et al, 2020), cytotoxic (Byun et al, 2022;Chan et al, 2022), anti-AD (Zhao et al, 2021), and anti-obesity activities (Kim et al, 2009), as well as antidiabetic potential (Surbala et al, 2020;Xie et al, 2020). Nevertheless, RUT is still unsuitable for direct clinical application due to its poor water solubility, moderate potency, or cytotoxicity (Lee et al, 2017;Luo et al, 2020).…”
Section: Introductionmentioning
confidence: 99%